Validation of a Novel Electronic Device for Medication Adherence Monitoring of Ambulatory Patients - Isabelle Arnet; Jean-Pierre Rothen; Kurt E. Hersberger (MDPI AG, 2019)
Several methods exist for measuring medication adherence. The Time4MedTM device (Adherence Innovations, Hong Kong) is a small, electronic card to affix on medication packaging that records date and time of intakes when a button is pushed. We aimed to validate the device with an emphasis on polypharmacy. Twenty volunteers used Time4MedTM devices with a virtual thrice daily intake over 14 days. Diary-recorded date and time were compared to electronically-stored events. Functionality, reliability and recovery for different stress conditions were calculated. User‘s acceptability was assessed with the System Usability Scale (SUS). Eleven elderly outpatients (mean age 80.2 ± 8.1 years) taking >3 medications daily used the device over 4 weeks. Volunteers logged 847 events. Functionality (100%), sensitivity (94.9%), specificity (99.4%) and recovery (100%) were high. Dropping the smart card and storing it in a refrigerator caused either the recording of false events or no recording at all. The mean SUS score was 82.6 (SD 14.8), demonstrating excellent acceptability. Satisfaction was very high for volunteers and patients, except for pushing the button. Time4MedTM devices are highly accurate in recording, retaining and delivering electronic data of multiple medication intake. They are well accepted by elderly patients. They can be recommended in clinical studies and for practitioners who desire to elucidate adherence patterns of ambulatory patients.